2-BFI Provides Neuroprotection Against Inflammation and Necroptosis in a Rat Model of Traumatic Brain Injury - Ni, Haibo; Rui, Qin; Lin, Xiaolong; Li, Di; Liu, Huixiang; Chen, Gang (Frontiers in Neuroscience, 2019)
Inflammation and programmed necrosis (necroptosis) are the 2 hallmark pathological changes after traumatic brain injury (TBI) that contribute to aggravated brain damage. 2-(2-Benzofuranyl)-2-imidazoline (2-BFI) has been shown to exert both anti-inflammatory and programmed cell death effects. Therefore, the aim of the present study was to evaluate the potential beneficial effects of 2-BFI in a rat model of TBI induced by a weight-drop device. 2-BFI or vehicle was given via intraperitoneal injection starting at 30 min post trauma and then twice daily for three consecutive days. Following a neurofunctional test at 72 hours after injury, histological, molecular, and immunohistochemistry analyses were performed on the pericontusional areas of the brain. 2-BFI treatment significantly attenuated neurological deficits, brain edema and blood-brain barrier permeability after TBI. Also, treatment with 2-BFI significantly reduced microglial activation, neutrophil infiltration, and proinflammatory cytokine interleukin (IL)-1β secretion, which is related to nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation after TBI. In addition, 2-BFI treatment markedly reduced cortical tissue loss as well as repressed TBI-induced increases in necroptosis and necroptosis-associated proteins, including receptor-interacting protein (RIP1), RIP3, and mixed linkage kinase domain-like (MLKL) in the pericontusional brain tissue. Taken together, these findings indicate that 2-BFI may be an effective neuroprotectant after brain trauma and warrants further study.